Decentralized Immunization Monitoring: Lessons Learnt from a Pilot Implementation in Kumbotso LGA, Kano State, Nigeria - Adam Attahiru; Yahaya Mohammed; Fiyidi Mikailu; Hyelshilni Waziri; Ndadilnasiya Endie Waziri; Mustapha Tukur; Bashir Sunusi; Mohammed Nasir Mahmoud; Nancy Vollmer; William Vargas; Yusuf Yusufari; Gustavo Corrêa; et al. (Vaccines)
Background: Immunization coverage in Nigeria is low, with many children missing out on important lifesaving vaccines. To enable a better understanding of contextual factors towards increasing uptake, we piloted a Decentralized Immunization Monitoring (DIM) approach in the Kumbotso local government area (LGA) of Kano state, Nigeria, to identify wards with low vaccination rates and understand why this is happening. The findings were used to improve routine immunization (RI) programs and reduce the number of unvaccinated children and children yet to receive their first dose of diphtheria–pertussis–tetanus (DPT) vaccine, referred to as Zero-Dose children (ZD). Methods: This study adopted a cross-sectional design approach using the Behavioural and Social Drivers of Vaccination (BeSD) framework and the Lot Quality Assurance Sampling (LQAS). The study population comprised caregivers of children aged 0–11 months and 12–23 months across the 11 wards in Kumbotso District, Kano State, Nigeria, using a segmentation sampling approach. The study covered 209 settlements selected using probability proportionate to size (PPS) sampling from the wards. Univariate and bivariate analyses were performed to show patterns and relations across variables. Results: Out of 418 caregivers surveyed, 98.1% were female. Delayed vaccination was experienced by 21.9% of children aged 4.5–11 months, while the prevalence of ZD was estimated at 26.8% amongst the older cohort (12–23 months). A total of 71.4% of the delayed group and 89.1% of the ZD group remained unvaccinated. Caregiver education, rural residence, and home births correlated with delayed/ZD status (p < 0.05). Logistic regression associated higher caregiver education with reduced delayed vaccination odds (OR:0.34, p < 0.001) and urban residence with lower ZD odds (OR:1.89, p = 0.036). The antigen coverages of BCG (81.5%), DPT3 (63.6%), and measles 1 (59.7%) all surpassed the national dropout thresholds. Kumbotso, Unguwar Rimi, and Kureken Sani wards were all identified as underperforming and therefore targeted for intervention. Negative vaccine perceptions (50% delayed, 53.6% ZD) and distrust in health workers (46.4% delayed, 48.2% ZD) were significant barriers, though the caregiver intent to vaccinate was protective (OR: 0.27, p < 0.001). The cost of accessing immunization services appeared to have a minor effect on coverage, as the majority of caregivers of delayed and ZD children reported spending less than 200 Naira (equivalent to USD 0.15) on transport. Conclusions: This pilot study highlighted the utility of LQAS and BeSD in identifying low-performing wards, barriers, and routine immunization gaps. Barriers included low caregiver education, rural residence, and negative vaccine perceptions/safety. Caregiver education and urban residence were protective factors against delayed and ZD vaccination, suggesting social and systemic barriers, particularly in rural and less educated populations. Antigen-specific coverage showed disparities, with dropouts for multi-dose vaccines exceeding the national thresholds of 10%. Targeted measures addressing education, trust, and systemic issues are needed. Findings emphasize decentralized monitoring, community engagement, and context-specific strategies to reduce ZD children and ensure equitable vaccination in Nigeria.